Analysis of an artificial zinc finger epigenetic modulator: widespread binding but limited regulation - Grimmer, Matthew R. (Oxford University Press, 2014)
Artificial transcription factors (ATFs) and genomic nucleases based on a DNA binding platform consisting of multiple zinc finger domains are currently being developed for clinical applications. However, no genome-wide investigations into their binding specificity have been performed. We have created six-finger ATFs to target two different 18 nt regions of the human SOX2 promoter; each ATF is constructed such that it contains or lacks a super KRAB domain (SKD) that interacts with a complex containing repressive histone methyltransferases. ChIP-seq analysis of the effector-free ATFs in MCF7 breast cancer cells identified thousands of binding sites, mostly in promoter regions; the addition of an SKD domain increased the number of binding sites ∼5-fold, with a majority of the new sites located outside of promoters. De novo motif analyses suggest that the lack of binding specificity is due to subsets of the finger domains being used for genomic interactions. Although the ATFs display widespread binding, few genes showed expression differences; genes repressed by the ATF-SKD have stronger binding sites and are more enriched for a 12 nt motif. Interestingly, epigenetic analyses indicate that the transcriptional repression caused by the ATF-SKD is not due to changes in active histone modifications.